Manufacturing of carbon nanotube-polystyrene filament for 3D printing: nanoparticle dispersion and electromagnetic properties - Baskakova, Kseniya I.; Okotrub, Alexander V.; Bulusheva, L. G.; Sedelnikova, Olga V. (Nanomanufacturing)
3D printing is a promising technology for creating polymer objects of a given architecture with specified functional properties. In fact, the choice of filaments for 3D printing is quite limited. Here, we report a process for producing polystyrene filaments with 0.0025–2 wt.% single-walled carbon nanotubes (SWCNTs) by extruding crushed polystyrene composites. The resulting filaments are characterized by a high uniformity of filler distribution and the absence of air pores. Comparison of microscopy data and electromagnetic properties of base composites and composite materials printed from filaments showed that extrusion and printing improve SWCNT dispersion. The proposed method can be used to create filaments for 3D printing of objects from various base polymers containing functional fillers up to the electrical percolation threshold and above.